The effect of civic sustainability-based civic education learning models on students' awareness of green citizenship - Pitria Sopianingsih; Nisrina Nurul Insani; Diana Noor Anggraini; Aura Sabrina Malika; Kim Vincent P Evangelista (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2026)
This research aims to develop and systematically evaluate a Civic Sustainability-integrated Civic Education learning model designed to cultivate students' Green Citizenship awareness within the digital era. The proposed pedagogical framework synthesises core civic concepts with contemporary sustainability imperatives, employing gamified project-based learning, interactive digital media, and comprehensive, authentic assessments to rigorously evaluate student processes, academic outcomes, and deliverables. Employing a quantitative correlational design, empirical data were gathered via a structured questionnaire administered to a cohort of 65 students at the Indonesia University of Education. Statistical analyses, including simple linear regression and Pearson's correlation coefficient, were conducted to assess the relationship between the model's implementation and increased environmental consciousness. The results yielded a statistically significant positive correlation (r = 0.580, p < 0.01) and a coefficient of determination (R² = 0.336), indicating that 33.6% of the variance in Green Citizenship awareness is directly attributable to the instructional model. These findings substantiate the efficacy of the Civic Sustainability-based paradigm in fostering ecological awareness, pro-environmental attitudes, and the capacity for active, responsible digital citizenship. Ultimately, this framework presents a strategic educational innovation within higher education, significantly contributing to the realisation of the Sustainable Development Goals (SDGs) and cultivating a generation profoundly committed to sustainability.